2013
DOI: 10.1007/s11883-013-0319-7
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Vascular Smooth Muscle Cell Function in Atherosclerosis

Abstract: Epigenetics involve heritable and acquired changes in gene transcription that occur independently of the DNA sequence. Epigenetic mechanisms constitute a hierarchic upper-level of transcriptional control through complex modifications of chromosomal components and nuclear structures. These modifications include, for example, DNA methylation or post-translational modifications of core histones; they are mediated by various chromatin-modifying enzymes; and ultimately they define the accessibility of a transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 82 publications
0
31
0
Order By: Relevance
“…As illustrated in Fig. 4c, roflumilast treatment decreased dimethylation of histone H3-lysine 4 (H3K4me2), an activating histone mark induced by inflammatory stimulation [28], at the VCAM-1 promotor 12 h after TNF-α treatment. Next, we investigated the effect of Epac and PKA activation on histone H3-lysine 4 dimethylation at the VCAM-1 promoter.…”
Section: Pde4 Inhibition and Epac Activation Reduce Epigenetic Histonmentioning
confidence: 90%
See 1 more Smart Citation
“…As illustrated in Fig. 4c, roflumilast treatment decreased dimethylation of histone H3-lysine 4 (H3K4me2), an activating histone mark induced by inflammatory stimulation [28], at the VCAM-1 promotor 12 h after TNF-α treatment. Next, we investigated the effect of Epac and PKA activation on histone H3-lysine 4 dimethylation at the VCAM-1 promoter.…”
Section: Pde4 Inhibition and Epac Activation Reduce Epigenetic Histonmentioning
confidence: 90%
“…Furthermore, roflumilast treatment had no effect on NF-κB translocation as well as VCAM-1 promoter activity, suggesting the involvement of regulatory components beyond the repression of transcription factor-dependent transactivation. As histone modifications control the accessibility of a transcription factor to a gene, they constitute a hierarchic upper-level of transcriptional control regulating gene expression in a specific manner [28]. Particularly methylation of H3K4 has been described as an activating histone mark that is highly enriched at the transcriptional start site (TSS) of active genes and induced following inflammatory stimulation [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies suggested that DNA methylation might participate in regulating VSMC phenotype and vascular remodeling. 24 Liu et al 25 reported a significant reduction in Tet2 expression in the neointima or coronary atherosclerotic plaques. Loss of Tet2 suppressed 5-hmC enrichment and affected the expression of VSMC differentiation marker genes, which in turn aggravated vascular remodeling.…”
Section: Zhuang Et Al Dnmt1 and Tet2 Regulate Vascular Remodeling 85mentioning
confidence: 99%
“…Given that Tet2 was the predominant DNA demethylation enzyme in arteries, 24 we firstly investigated the expression of Tet2 among 3 groups. Using our panel of mouse aorta samples, we tested the abundance of RNA transcripts and protein.…”
Section: Dnmt Inhibition Dynamically Regulated Dna Methylation and Tementioning
confidence: 99%
See 1 more Smart Citation